Assessing the Relationship between PTSS in Childhood Cancer Survivors and Their Caregivers and Their Quality of Life. (30th September 2020) - de Castro, Elisa Kern; Crespo, Carla; Barros, Luísa; Armiliato, Maria Júlia; Gregianin, Lauro
Abstract: Childhood cancer is a traumatic experience for survivors and their families. The experience of this disease affects survivors' and families' quality of life, even years after it occurs. The purpose of the present study was to assess if the caregivers' posttraumatic stress symptoms mediated the associations between survivors' posttraumatic stress symptoms and caregivers' quality of life, in a sample of 46 dyads of caregivers and childhood cancer survivors. Survivors and caregivers completed the PCL-5, and caregivers completed the WHOQOL-bref. Results showed that survivors' and caregivers' posttraumatic stress symptoms scores and caregivers' quality of life were associated. The caregivers' posttraumatic stress symptoms mediated the relationship between survivors' posttraumatic stress symptoms and caregivers' quality of life. Knowing posttraumatic stress symptoms direct and indirect effects on caregivers' quality of life contributes to understand their experience and to develop intervention strategies with this population.